2017
DOI: 10.1093/aje/kwx277
|View full text |Cite
|
Sign up to set email alerts
|

Possible Mediation by Methylation in Acute Inflammation Following Personal Exposure to Fine Particulate Air Pollution

Abstract: Air pollution may increase cardiovascular and respiratory risk through inflammatory pathways, but evidence for acute effects has been weak and indirect. Between December 2014 and July 2015, we enrolled 36 healthy, nonsmoking college students for a panel study in Shanghai, China, a city with highly variable levels of air pollution. We measured personal exposure to particulate matter with an aerodynamic diameter less than or equal to 2.5 μm (PM 2.5 ) continuously for 72 hours preceding each of 4 clinical visits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 55 publications
4
41
1
2
Order By: Relevance
“…Regarding the effects of air pollution on inflammation by epigenetic modulation, it was reported that the long-term exposure (annual average in the preceding year) to fine particulate matter (PM 2.5 ) was associated with increased TNF-α expression through a reduction in TNF-α gene methylation in women [176]. In addition, changes in TNF methylation were proposed to mediate acute inflammation following personal exposure to fine particulate air pollution [177]. Consistently, adverse cardiac autonomic dysfunctions by PM 2.5 exposure was partially related to methylation changes in the inflammatory TLR2 gene [178].…”
Section: Climatementioning
confidence: 99%
“…Regarding the effects of air pollution on inflammation by epigenetic modulation, it was reported that the long-term exposure (annual average in the preceding year) to fine particulate matter (PM 2.5 ) was associated with increased TNF-α expression through a reduction in TNF-α gene methylation in women [176]. In addition, changes in TNF methylation were proposed to mediate acute inflammation following personal exposure to fine particulate air pollution [177]. Consistently, adverse cardiac autonomic dysfunctions by PM 2.5 exposure was partially related to methylation changes in the inflammatory TLR2 gene [178].…”
Section: Climatementioning
confidence: 99%
“…Various types of cellular stress seem to affect epigenetic alterations that may lead to deleterious consequences. Exposure to fine particle air pollution affects DNA methylation status in blood cells [ 178 , 179 , 180 , 181 , 182 , 183 ] and placenta [ 184 ]. Cigarette smoking has adverse effects on health and is associated with changes in epigenetic marks.…”
Section: Epigenetics and Agingmentioning
confidence: 99%
“…For example, NO 2 may cause lung cancer [ 8 ], PM has been associated with increased blood pressure (BP), and a certain concentration of ozone has been associated with decreased BP [ 9 ]. There is an association between PM 2.5 and inflammation [ 10 ]. PM 2.5 can also increase the incidence of various respiratory and circulatory diseases [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%